Update on the application of mesenchymal stem cell-derived exosomes in the treatment of Parkinson's disease: A systematic review - Liu, Shu-fen; Li, Lin-yi; Zhuang, Jian-long; Li, Mi-mi; Ye, Li-chao; Chen, Xiang-rong; Lin, Shu; Chen, Chun-nuan (Frontiers in Neurology, 2022)
Parkinson's disease (PD) has become the second largest neurodegenerative disease after Alzheimer's disease, and its incidence is increasing year by year. Traditional dopamine replacement therapy and deep brain stimulation can only alleviate the clinical symptoms of patients with PD but cannot cure the disease. In recent years, stem cell therapy has been used to treat neurodegenerative diseases. Many studies have shown that stem cell transplantation has a therapeutic effect on PD. Here, we review recent studies indicating that exosomes derived from mesenchymal stem cells also have the potential to treat PD in animal models, but the exact mechanism remains unclear. This article reviews the mechanisms through which exosomes are involved in intercellular information exchange, promote neuroprotection and freely cross the blood-brain barrier in the treatment of PD. The increase in the incidence of PD and the decline in the quality of life of patients with advanced PD have placed a heavy burden on patients, families and society. Therefore, innovative therapies for PD are urgently needed. Herein, we discuss the mechanisms underlying the effects of exosomes in PD, to provide new insights into the treatment of PD. The main purpose of this article is to explore the therapeutic potential of exosomes derived from mesenchymal stem cells and future research directions for this degenerative disease.